Generalized periodic solutions of ordinary linear differential equations in the Colombeau algebra - Ligęza, Jan (Annales Mathematicae Silesianae, 1997)
It is shown that from the fact that the unique periodic solution of homogeneous system of equations is the trivial one it follows the existence of periodic solutions of nonhomogeneous systems of equations in the Colombeau algebra.